Anomalous, extreme weather disrupts obligate seed dispersal mutualism: snow in a subtropical forest ecosystem. - Zhou, Y; Newman, C; Chen, J; Xie, Z; Macdonald, D (2013)
Ongoing global climate change is predicted to increase the frequency and magnitude of extreme weather events, impacting population dynamics and community structure. There is, however, a critical lack of case studies considering how climatic perturbations affect biotic interactions. Here, we document how an obligate seed dispersal mutualism was disrupted by a temporally anomalous and meteorologically extreme interlude of unseasonably frigid weather, with accompanying snowstorms, in subtropical China, during January-February 2008. Based on the analysis of 5892 fecal samples (representing six mammalian seed dispersers), this event caused a substantial disruption to the relative seed dispersal function for the raisin tree Hovenia dulcis from prestorm 6.29 (2006) and 11.47 (2007), down to 0.35 during the storm (2008). Crucially, this was due to impacts on mammalian seed dispersers and not due to a paucity of fruit, where 4.63 fruit per branch were available in January 2008, vs. 3.73 in 2006 and 3.58 in 2007. An induced dietary shift occurred among omnivorous carnivores during this event, from the consumption fruit to small mammals and birds, reducing their role in seed dispersal substantially. Induced range shift extinguished the functionality of herbivorous mammals completely, however, seed dispersal function was compensated in part by three omnivorous carnivores during poststorm years, and thus while the mutualism remained intact it was enacted by a narrower assemblage of species, rendering the system more vulnerable to extrinsic perturbations. The storm's extended effects also had anthropogenic corollaries - migrating ungulates becoming exposed to heightened levels of illegal hunting - causing long-term modification to the seed dispersal community and mutualism dynamics. Furthermore, degraded forests proved especially vulnerable to the storm's effects. Considering increasing climate variability and anthropogenic disturbance, the impacts of such massive, aberrant events warrant conservation concern, while affording unique insights into the stability of mutualisms and the processes that structure biodiversity and mediate ecosystem dynamics.